Sustaining Culinary Legacies: Innovation and Sustainability in the Management of Legendary Culinary Businesses - Inlando, Greeneza Armyes Hinggilta; Hartati, Sri (PT. EQUATOR SINAR AKADEMIA, 2025)
Legendary culinary delights hold a unique appeal, built upon consistent taste and strong emotional connections with consumers. However, navigating the dynamic culinary landscape requires a deep understanding of evolving consumer preferences, innovative strategies, and sustainable practices. This research aims to investigate how product innovation and sustainability strategies can be effectively implemented in the management of legendary culinary businesses. A case study of a prominent café in Bandung, referred to as “Café X” for this research, will be used to illustrate these principles. Employing a qualitative approach, this research explores the business management processes, challenges, and opportunities faced by such establishments. Data collection involved in-depth interviews, surveys, and the analysis of primary and secondary data. Through the application of TOWS and Business Model Canvas (BMC) frameworks, this research found that the sustainability of a legendary culinary business hinges on its ability to adapt to evolving market trends, leverage technology, and implement product innovations while preserving authentic taste. Key strategies for enhancing market attractiveness, particularly among younger generations, include fostering strategic partnerships, embracing digital marketing, and developing healthy product offerings. The findings of this research can serve as a valuable reference for designing effective innovation strategies and supporting the continuity of legendary culinary businesses across Indonesia, while also providing guidance for business professionals in navigating the challenges of a dynamic market.